Upaya Meningkatkan Konsentrasi Belajar Melalui Metode Joyful Learning Berbasis Ice Breaking Di SD N 4 Dongos - Nur Afif Wahyudin; Muhammad Rozikul Afnani; Syailin Nichla Choirin Attalina (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2023)
The low concentration of student learning is caused by the inaccuracy of the learning method used by the teacher when delivering material. The purpose of this study was to increase the learning concentration of class III students at SDN 04 Dongos through the use of the Ice Breaking-based Joyful Learning method on flat shapes. This research is included in quantitative research with the type of experimental research with data collection techniques in the form of questionnaires, observations and interviews. The results to be achieved in this study are the use of the joyful learning method based on ice breaking in learning to increase student learning concentration.